Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1096/fasebj.3.10.2546848
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of neuronal receptors

Abstract: This article describes ways in which receptors, key components of signal propagation through a synapse, can mediate changes in that propagation. Changes occur at four levels: in the signal-transducing capability of a single receptor molecule, in the number of receptors per cell, in the subcellular placement of receptor molecules, and in the cytoarchitecture of receptor-rich regions. The ability of receptors to shift between different desired states is called plasticity, and such shifts can be long-lived as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Plasticity of neurotransmitter receptor number or distribution is a key component of the compensatory neuronal response to denervation and changes in afferent activity (Klein et al, 1989). Although classically associated with the peripheral nervous system (Lømo and Rosenthal, 1972;Frank et al, 1975), receptor plasticity of this kind has also been demonstrated in the CNS.…”
Section: Abstract: Excitatory Amino Acid Receptors; Immunocytochemismentioning
confidence: 99%
“…Plasticity of neurotransmitter receptor number or distribution is a key component of the compensatory neuronal response to denervation and changes in afferent activity (Klein et al, 1989). Although classically associated with the peripheral nervous system (Lømo and Rosenthal, 1972;Frank et al, 1975), receptor plasticity of this kind has also been demonstrated in the CNS.…”
Section: Abstract: Excitatory Amino Acid Receptors; Immunocytochemismentioning
confidence: 99%
“…In addition to developmental changes of NMDA receptor subunit expression in culture, the adaptive changes in the number and/or the function of receptors following prolonged treatments with neurotransmitter (Klein et al, 1989;Hadcock and Malbon, 1991) were also reported for the NMDA receptor. In fact, treatment of cultured cerebellar granule cells at 5 days in vitro (DIV5) with 100 ,iM NMDA for 24 h evoked a pronounced decrease in NMDA-stimulated 45Ca2~fluxes accompanied by a reduction in NR 1, NR2A, and NR2B subunit mRNA levels and NR1 subunit protein (Resink et al, 1996).…”
mentioning
confidence: 99%
“…Regulation of neurotransmitter signal transduction at the level of the synaptic receptor is a potentially important mechanism of synaptic plasticity. A substantial body of evidence now suggests that phosphorylation events regulate the functions of both G-protein<oupled receptors and ligand-gated ion channel receptors (reviewed by Sibley et al, 1987;Klein et al, 1989;Huganir and Greengard, 1990). The functional consequences of G-protein<oupled receptor phosphorylation have been extensively studied using the &adrenergic receptor (&AR)…”
mentioning
confidence: 99%